Efektivitas Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) terhadap Adat dan Kebiasaan Masyarakat di Desa Adat Menyali Kabupaten Buleleng - I Putu Pradita Wiradinatha; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2022)
Indonesia is a country with a large and diverse archipelago with many cultures, customs and traditions in various forms. An area that has unique customs is Bali and has many different traditional rituals, but right now the world is being hit by the Covid19 pandemic which requires PPKM, such as in the Mengali Traditional Village, Buleleng Regency. This research aims to discuss the effectiveness of the implementation of Community Activity Restrictions (PPKM) on the habits and customs of the community as well as the government's efforts in accelerating the control of Covid19 in the traditional village of President Menyali, Buleleng Regency. This research uses empirical legal research with a sociological legal approach. The sources of legal materials for this research consist of the main sources, including the Minister of Home Affairs Regulation no. 15 of 2021 concerning the Implementation of Restrictions on Community Activities for Corona Virus Disease 2019 and Governor's Regulation No. 12 of 2021 concerning the Enforcement of Restrictions on Community Activities Covid19 in a New Era of Life in the Province of Bali. As well as supporting legal materials taken from law books and legal journals related to this research. Interview techniques and note-taking techniques were used as data collection techniques. The result of this research is that the influence of PPKM on the habits of the people in the Mengali Traditional Village, Buleleng Regency is still very inefficient so that PPKM tightening covers several areas and other customary activities, and the role of local governments is less helpful in reducing these impacts. This pandemic is because people don't obey it. The government's appeal to implement PPKM policies such as long-distance travel requires showing a vaccine card.